Inactivating Food Microbes by High-Pressure Processing and Combined Nonthermal and Thermal Treatment: A Review. (24th August 2022) - Nema, Prabhat K.; Sehrawat, Rachna; Ravichandran, Chandrakala; Kaur, Barjinder Pal; Kumar, Anit; Tarafdar, Ayon
Abstract : High-pressure processing (HPP) is a mild technology alternative to thermal pasteurization and sterilization of different food products. HPP has emerged to provide enormous benefits to consumers, i.e., mildly processed food and additive-free food. It effectively retains bioactive compounds and extends the shelf life of food commodities by inactivating bacteria, yeast, mold, and virus. The limitation of HPP in inactivating spores can be overcome by using other thermal and nonthermal processing sequentially or simultaneously with HPP. This review summarizes the applications of HPP in the fruits and vegetables, dairy, meat, fish, and poultry sector. It also emphasizes microbial food safety and the effectiveness of HPP in the load reduction of microorganisms. Comprehensive information about the synergistic effect of HPP with different techniques and their effectiveness in ensuring food safety is reported. The summarized data would be handy to interested researchers and industry personnel.